Determinants of Voluntary Carbon Disclosure in Indonesian Company: Greenwashing Risks - Mega Silvia; Fei Guo (International Journal of Management, Accounting and Economics, 2023)
There is a greenwashing risk in voluntary carbon disclosure and there are no adequate regulations for stakeholder protection. So, there is a risk of providing information that can mislead stakeholders in making decisions. This research will analyze the determinants of carbon emission disclosure by considering the risk of greenwashing in Indonesian companies. This study also uses the ratification period of Presidential Regulation No.98 to analyze its contribution to the relationship between variables. It is necessary to study the role and ability of regulators to intervene in Indonesian companies. This study uses a random effect model to examine the influence between variables. The total data sample for this study is 876 (firm-years). This study also uses the Difference in Difference (DID) method to address the risk of endogeneity, and to evaluate the effect between research variables by adding the ratification period to Presidential Regulation No.98. Empirical results show that corporate governance has a positive effect on carbon emissions disclosure. Changes in carbon emissions has a positive effect on carbon emissions disclosure. The results show the period of ratification of Presidential Regulation No.98 can strengthen the relationship between corporate governance and carbon emissions disclosure, and can strengthen the relationship between changes in carbon emissions and carbon emissions disclosure when companies fail to mitigate carbon emissions.